Adoption of solar-powered pumps in agriculture: insights from smallholders in Burkina Faso - Mamadou Sanogo; Roland Yonaba; Amadou Keïta; Abdou Lawane; Bruno Barbier; Abdou Maman Galadima Aminatou; Isidore Bazié; Sabine Ouarmé (Discover Agriculture)
Abstract Irrigation plays a critical role in agricultural intensification and productivity enhancement, especially in rainfall-scarce environments. Solar pumps have emerged as promising solutions for controlling energy consumption. This study examines the factors influencing the adoption of solar-powered irrigation pumps among horticultural farmers in the Kadiogo Province, located in the Centre Region in Burkina Faso, a landlocked Sahelian country within West Africa. Within the framework of a solar pump subsidy program, a random sample of 200 farmers, including 42% of adopters and 58% of non-adopters of solar pumps for irrigation. A logit model revealed that factors such as gender, membership in rural organizations, farm size, agricultural income and perceived ease of manutention significantly affect the likelihood of adopting solar pumps. Additionally, level of education and purchase cost also influence adoption probabilities. These findings suggest that targeted interventions, focusing on enhanced educational outreach, subsidization of purchase costs and support of rural organizations could trigger widespread adoption of solar-powered pumps in smallholder communities, thereby improving agricultural productivity and resilience in small-scale farming communities.